EKSPRESI KEBEBASAN DIRI DALAM KARYA SENI LUKIS KONTEMPORER - ALLEN SAPUTRA, Drs. Abd. Hafiz, M.Pd, Drs. Erfahmi, M.Sn. (Serupa The Journal of Art Education, 2016)
Interest visualize the freedom of self expression in the works of contemporary painting. Humans are given the freedom of expression in any circumstances affect their lives. By expressing man makes the burden of thinking becomes lighter and can even find the solution of the problems it faces. In essence, no man is free, because human beings are bound in their activities. Ten paintings contemporary style that is created through a process that begins with the search for ideas, and the idea gained poured out in the form of sketches, followed by visualizing the form of painting.1). "Tumbuh dari Dalam", 2). "Bayangan", 3). "Control", 4). "Sendiri", 5). "Untitled" 6). "Tenang", 7). "Passion", 8). "Freedom", 9). "Brain # 1", 10). "Brain # 2". Visualization idea pour writer is the freedom of self expression and how this writer a freedom based on the experience that the author experienced.Kata kunci : Seni Lukis, Kontemporer, Ekspresia